Risks of Autologous Abdominal Free Flap Breast Reconstruction in Patients With Elevated Body Mass Index - Nathaniel A. Teitler, MD; Courtney J. Doherty, BS; Madalyn R. Adams, MD; Anna A. Podber, MD; Peter M. Granger, MD; Kaeli K. Samson, MPH, MA; Sean C. Figy, MD; Shannon L. Wong, MD; Heidi H. Hon, MD (Plastic and Reconstructive Surgery, Global Open)
Background:. Obesity is widely recognized as a significant risk factor for postoperative complications of breast reconstruction. Despite extensive research, there remains a lack of consensus regarding the specific complications and outcomes experienced by patients with obesity who undergo deep inferior epigastric perforator (DIEP) flap reconstruction. To provide a clearer understanding of the challenges faced by patients with obesity, we present a single-center outcome analysis of individuals who underwent DIEP flap reconstruction. Methods:. A cohort of 194 patients who underwent at least 1 DIEP flap was retrospectively analyzed at the University of Nebraska Medical Center utilizing electronic medical records. Patients who underwent DIEP flap breast reconstruction were organized into 5 categories using World Health Organization weight status by body mass index (BMI) obtained from the day of surgery. Surgical complications within 120 days and postsurgical complication-related procedural interventions were also evaluated and compared. Comparisons of variables of interest between weight groups were assessed using Mantel–Haenszel chi-square tests or Spearman correlations. Results:. Increases in patient weight category were associated with increased length of operation (P = 0.003), increased rates of breast fat necrosis (P = 0.04), breast wound dehiscence (P = 0.01), abdominal wound dehiscence (P = 0.02), numbers of abdominal complications (P = 0.001), and rates of requiring an intervention (P = 0.03). Conclusions:. The findings imply that higher BMI values may lead to a higher likelihood of postoperative complications and the need for intervention. It is crucial for patients with obesity to be aware of the elevated risk associated with rising BMI values.